Effects of Inventory Management on Service Delivery in Public Sector: A Case of Office of Registrar of Political Parties - Sama, Hamisi Kileo; Mdemu, Renhada (Rescollacom (Research Collaborations Community), 2024)
This study was intended to assess the effect of inventory management on services delivery in public sector: A case in Office of Registrar of Political Parties. The specific objective was to investigate the influence of inventory management on service delivery in public sector. The study employed a cross-section research design and a sample of 44 respondents was selected using a simple randomly sampling technique. Data collection methods included questionnaire and interview. Data were analyzed using descriptive statistics and correlation analysis. The study finding shows that there is a positive relationship between the inventory management and service delivery. The study concludes that inventory management was important factors in inventory management that influence service delivery in Office of Registrar of Political Parties. Therefore, the study recommends that, to improve inventory management on service delivery, the study recommends that, the Office of Registrar of Political Parties could ensure technology adoption regulatory environment, and physical infrastructure and facilities. Also, further research in the academic study of the effect of inventory management on service delivery in the public sector could explore several areas to deepen understanding and address gaps in existing knowledge. Some potential areas for further research can investigate the impact of emerging technologies such as Internet of Things (IoT), artificial intelligence (AI), and blockchain on inventory management practices and service delivery in the public sector.